Habilidades gerenciales de los directivos en el gobierno autónomo descentralizado municipal del cantón Latacunga. - Pilaguano Ayala, Byron Esteban (2023)
Management skills have taken relevance in the business environment in the private sectors, since allowing the competitive and productive development of these entities. While in the public sector their relevance is low, which is reflected in the objectives fulfillment and in the nonconformities of their external clients (citizens). For this reason, this research aims to evaluate the managerial skills in the Autonomous Decentralized Municipal Government of Latacunga city, for which we proceeded to conduct the analysis of a variable called Managerial Skills, The reliability and correlation of the constructs was determined with the Confirmatory Factor Analysis (CFA) using the SPSS statistical system, which yielded values of 0.781 in the KMO test and a value of 0.00 in Bartlett's sphericity test, the same values that gave the research a pass. The research method applied had a descriptive quantitative approach, in which the survey technique was applied, and the instrument was a questionnaire divided into two sections, the first section collected sociodemographic information while the second section collected information on Managerial Skills, the questionnaire was applied to 30 employees. This research result showed that the conceptual skills, related to the Strategy construct, is the lowest with a value of 4.15, considering within the scale the value 1 as the lowest and 5 as the highest. Meanwhile, human skills, linked to the Intra-strategy construct, had a value of 4.30, positioning it as the highest or most relevant within the managerial skills of municipal government managers, and finally, technical skills, linked to the Personal Efficacy construct, had a value of 4.27. In fact, an action plan was proposed to improve and strengthen managerial skills, both conceptual, human and technical, which are fundamental for all managers.